Big-fish-little-pond effects on gymnastics self-concept: Social comparison processes in a physical setting - Chanal, J; Marsh, H; Sarrazin, P; Bois, J (Human Kinetics, 2005)
In sport/exercise contexts, individuals use the performances of others to evaluate their own competence. In big-fish-little-pond effect (BFLPE) in educational settings, academic self-concept is positively predicted by one's academic achievement but negatively predicted by the average achievement of others in one's school or class. Participation in programs for academically gifted students leads to lower self-concept. In apparently the first test of the BFLPE in the physical domain, multilevel models of responses by 405 participants in 20 gymnastics classes supported these predictions. Gymnastics self-concept was positively predicted by individual gymnastics skills, but negatively predicted by class-average gymnastics skills. The size of this negative BFLPE grew larger during the 10-week training program (as participants had more exposure to the relative performances of others in their class), but did not vary as a function of gender, age, or initial gymnastics skills. © 2005 Human Kinetics Publishers, Inc.